PENGARUH PEMBELAJARAN DARING DAN MINAT BELAJAR TERHADAP KREATIVITAS MAHASISWA PADA MATA KULIAH KEWIRAUSAHAAN - Anggreni, Ni Luh Putu Yesy; Suparyana, Pande Komang (Lentera: Jurnal Ilmiah Kependidikan, 2021)
Online learning provides solutions for the world of education during the Covid-19 pandemic. However, there are many problems faced in the online learning process, especially for students in promoting innovation and creativity in the Entrepreneurship course. This study aims to analyze the effect of online learning and interest in learning together on student creativity in entrepreneurship courses simultaneously and partially at the PGRI Mahadewa University of Indonesia. Data were analyzed by statistical analysis of multiple linear regression with two predictors. The number of samples in the study were 94 students. Based on data analysis and research findings, several things can be concluded as follows: 1) Student creativity in entrepreneurship courses at PGRI Mahadewa University Indonesia is significantly influenced by online learning variables and interest in learning simultaneously; 2) Partially online learning and interest in learning make a significant contribution to student creativity in entrepreneurship courses at the PGRI Mahadewa University of Indonesia. Thus, the findings of this study can be used as positive information for lecturers who teach entrepreneurship subjects related to the factors that affect the level of student creativity.